1993
DOI: 10.1128/iai.61.8.3318-3326.1993
|View full text |Cite
|
Sign up to set email alerts
|

Repeats in an extracellular protein of weakly pathogenic strains of Streptococcus suis type 2 are absent in pathogenic strains

Abstract: Streptococcus suis type 2 strains that are pathogenic for pigs produce a 110-kDa extracellular protein factor (EF). Nonpathogenic and weakly pathogenic strains do not produce EF or produce a protein (EF*) that is immunologically related to EF. To study the pathogenesis of S. suis type 2 in pigs and to develop tools and methods for the control of S. suis type 2 infections, we cloned and characterized the genes encoding EF and various EF* proteins. Analysis of the deduced amino acid sequences showed that the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 28 publications
5
46
0
1
Order By: Relevance
“…The most frequently observed form of the sao gene was sao-M, which is the medium-sized version at $1.7 kb. The results resemble those reported by Smith et al (1993). In that study, the authors also found EF, a derivative of EF Ã lacking the repeat units at its C-terminus, and was correlated with increased virulence (Smith et al, 1993).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The most frequently observed form of the sao gene was sao-M, which is the medium-sized version at $1.7 kb. The results resemble those reported by Smith et al (1993). In that study, the authors also found EF, a derivative of EF Ã lacking the repeat units at its C-terminus, and was correlated with increased virulence (Smith et al, 1993).…”
Section: Discussionsupporting
confidence: 83%
“…The results resemble those reported by Smith et al (1993). In that study, the authors also found EF, a derivative of EF Ã lacking the repeat units at its C-terminus, and was correlated with increased virulence (Smith et al, 1993). Therefore, it would be of interest to determine whether or not the present deletion variants in Sao proteins have any correlation with their pathogenicity of the organisms.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…significantly variant genes, respectively, including 88 genes shared by all three avirulent strains (additional file 3). The virulence-related epf gene cluster [10,11], which encodes extracellular protein factor (EF; a putative virulence marker that widely exists in virulent strains) was absent in the avirulent strains [12]. Consistent with previous research, this gene cluster is present in all of the analyzed virulent strains.…”
Section: Deletions and Significantly Variant Genessupporting
confidence: 88%
“…must have 5% carbon dioxide for growth. canis as a commensal organism which can cause opportunist pyogenic infections (Laughton 1948).…”
Section: Introductionmentioning
confidence: 99%